Processes that drive the population structuring of Jenynsia lineata (Cyprinidontiformes, Anablepidae) in the La Plata Basin - Briñoccoli, Yanina Florencia (2021)
1. The distribution of genetic diversity across a species distribution range is rarelyhomogeneous, as the genetic structure among populations is related to the degreeof isolation among them, such as isolation by distance, isolation by barrier,and isolation by environment.2. Jenynsia lineata is a small viviparous fish that inhabits a wide range of habitats inSouth America. To decipher the isolation processes that drive population structuringin J. lineata, we analyzed 221 sequences of the mitochondrial cytochrome c oxidaseI gene (COI), from 19 localities. Then, we examined the influence of the threemost common types of isolation in order to explain the genetic variation found inthis species.3. Our results revealed a marked structuration, with three groups: (a) La Plata/Desaguadero Rivers (sampling sites across Argentina, Uruguay, and SouthernBrazil), (b) Central Argentina, and (c) Northern Argentina. A distance-basedredundancyanalysis, including the explanatory variables geographical distances, altitude,latitude, and basin, was able to explain up to 65% of the genetic structure.A variance partitioning analysis showed that the two most important variablesunderlying the structuration in J. lineata were altitude (isolation by environment)and type of basin (isolation by barrier).4. Our results show that in this species, the processes of population diversificationare complex and are not limited to a single mechanism. The processes that play aprominent role in this study could explain the high rate of diversity that characterizesfreshwater fish species. And these processes in turn are the basis for possiblespeciation events.